Conference report: Naigeon and the Mémoires historiques et philosophiques sur la vie et les ouvrages de Denis Diderot, 28th March 2025, All Souls College, University of Oxford - Rowe, Holly (Diciottesimo Secolo, 2025)
Report of the conference «Naigeon and the Mémoires historiques et philosophiques sur la vie et les ouvrages de Denis Diderot», organised by Caroline Warman (Jesus College, University of Oxford) on 28th March 2025 at All Souls College, University of Oxford.